Faktor-Faktor yang Mempengaruhi Perilaku Diet Hipertensi pada Lansia yang Akan Rawat Jalan di Rumah Sakit Umum Bhakti Asih Tangerang - Thomas Ichsan Cahya; Asha Grace Sicilia; Riska Reviana; Harun Wahyudi; Reni Afriyani (Journal of Educational Innovation and Public Health, 2025)
Background: Hypertension in the elderly is caused by degenerative processes and triggering factors such as poor diet, smoking, and alcohol consumption. The WHO identifies hypertension as a major risk factor for cardiovascular diseases that can lead to serious complications such as stroke and heart disease. Objective: To identify the factors influencing dietary behavior related to hypertension in elderly patients who will be treated as outpatients in the Orchid Room of Bhakti Asih General Hospital, Tangerang, focusing on knowledge, attitudes, health worker support, and family support. Research Method: This quantitative study uses primary data from questionnaires with a Field Research method. The sample consists of 40 respondents, and data analysis was conducted using the Chi-Square Test. Research Results: The results of the Chi-Square test show a significant relationship between knowledge (ρ = 0.000), attitudes (ρ = 0.012), health worker support (ρ = 0.009), and family support (ρ = 0.000) towards dietary behavior related to hypertension in the elderly. Conclusion: Overall, knowledge, attitudes, health worker support, and family support influence dietary behavior related to hypertension in the elderly, which can impact the effective management of hypertension and prevent further complications. Recommendation: For future researchers, this study has limitations, and it is hoped that further research can develop this topic with a more comprehensive research methodology approach.